Polymorphisms Within DNA Double-Strand Breaks Repair-Related Genes Contribute to Structural Chromosome Abnormality in Recurrent Pregnancy Loss - Cheng, Zhenbo; Cheng, Dehua; Li, Jiancheng; Guo, Lihuang; Zhang, Wei; Zhang, Conghui; Liu, Yangxu; Huang, Yue; Xu, Keqian (Frontiers in Genetics, 2021)
A B S T R A C T Background: Structural chromosome abnormality (SCA) is an important cause of human diseases, including recurrent pregnancy loss (RPL). DNA double-strand breaks (DSBs) repair-related genes play critical roles in SCA. The present study aims to investigate the potential contribution of DSBs repair-related gene polymorphisms to SCA. Methods: Fifty-four affected RPL individuals with SCA, 88 affected RPL individuals without SCA, and 84 controls were analyzed. Targeted whole-exome sequencing (WES) was used for screening single nucleotide polymorphisms in six DSBs repair-related genes (EP300, XRCC6, LIG4, XRCC4, PRKDC and DCLRE1C), and validation was performed by Sanger sequencing. Finally, we detected the frequency of radiation-induced chromosome translocations in no SCA samples with significant polymorphisms by fluorescence in situ hybridization (FISH). Results: A total of 35 polymorphisms have been identified and confirmed. Frequencies of EP300 rs20551, XRCC6 rs132788 and LIG4 rs1805388 were significantly different between SCA RPL and no SCA RPL (P = 0.030, 0.031 and 0.040 respectively). Frequencies of those three gene polymorphisms between SCA RPL and controls also were significantly different (P = 0.017, 0.028 and 0.029 respectively). Moreover, the frequency of the G allele at rs20551 locus, the T allele at rs132788 locus and the A allele at rs1805388 locus was significantly higher in SCA RPL than no SCA RPL (OR = 3.227, P = 0.005; OR = 1.978, P = 0.008 and OR = 1.769, P = 0.036 respectively) and controls (OR = 7.130, P = 0.000; OR = 2.157, P = 0.004; OR = 2.397, P = 0.003 respectively). Additionally, the frequency of radiation-induced translocation in no SCA samples with rs20551, rs132788 or rs1805388 was significantly higher compared with the wild type samples (P = 0.015, 0.012 and 0.007 respectively). Conclusion: Our results suggest that rs20551, rs132788 and rs1805388 might be associated with the risk of SCA. Larger scales of genetic variations studies and functional experiments are necessary to further confirm these findings.